Architecture for ES Receiver Systems Targeted at Commercial Wireless Communications - Plessis,Warren Paul du (2013)
ABSTRACT: Modern electronic support (ES) systems are descended from systems intended for the detection of small numbers of high-power radar systems, and are thus not suitable for the low-power transmitters and dense signal environments typical of commercial communication networks. A new ES-system architecture is proposed to allow the detection of large numbers of low-power emitters and the estimation of their angle of arrival. The proposed architecture has a number of benefits including versatility, suitability for deployment on airborne platforms, and modularity.